The Relationship Between Technology Advancments And Organisational Preformance : A Study In Malaysia - Loh, Swit-Zanne (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research seeks to examine the relationship between technology advancements and organisational performance. Technology advancement, can be divided into three categories which is technology orientation, access to technology and knowledge resources. The three elements have been used to examine the organisational performance in terms of financial performance, sales performance and production performance. Besides that, this study is moderated by innovation culture to examine if it affects technology advancements and organisational performance. A total of six hypotheses were formulated and experimented among the organisations in the small medium enterprise (SME) industry in Malaysia. Data was accumulated from respondents who are employees working in small medium enterprises through the 7- point Likert scale and 5-point Likert scale questionnaire. Hence, the findings provide some support for SMEs in Malaysia to achieve a better performance by embracing the advancements of technology instead of looking at it as a hurdle.